Peran Resiliensi dalam Mengurangi Stres Mahasiswa Kepaniteraan Klinik: Tinjauan Pustaka - Syafira Salsabila; Lisiswanti, Rika; Yuningrum, Hesti; Ramadhian, Muhammad Ricky (Medula, 2024)
The transition from the preclinical to the clinical phase of medical education, characterized by a significant difference in the learning system and increased demands, often leads to stress among medical students. A very packed schedule, tight deadlines, and the need to adapt to a dynamic clinical environment are primary stressors for medical students during their clerkship. Prolonged high levels of stress can negatively impact mental health, academic performance, and the quality of medical care, increasing the risk of medical malpractice. Resilience, defined as an individual's ability to recover from difficult situations, has proven to be a crucial protective factor in mitigating the effects of stress. Resilience is a dynamic process demonstrated when individuals take adaptive actions in the face of adversity. It is not a genetic trait but a behavior that can be developed by strengthening the factors that support it. These factors can be internal, external, or interpersonal. One way to enhance resilience is through resilience training programs that involve interactive, independent, and reflective workshops. High levels of resilience among medical students are associated with increased subjective well-being, reduced stress levels, and a more positive perception of quality of life and the educational environment. Therefore, by enhancing resilience, medical students can better cope with the pressures of clerkship, maintain mental health, and optimize academic performance in medical care.